Prognostic factors affecting the mortality of 2nd and 3rd degree burn injuries at a tertiary care center in Indonesia - Ishandono Dachlan; Khoirul Anam (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
About two million people suffer from burn injuries in the United States eachyear, with 100,000 hospitalized in the burn unit. Around 1000 patients sufferfrom severe burn injuries, with each year average of 300 deaths. Improvementsin the understanding of the prognostic factors affecting burn injuries over thepast decades have led to advances in medical and surgical treatment. However,comprehensive data on the factors affecting burn injuries in Indonesia havenot been available, yet. The aim of the study was to investigate the prognosticfactors affecting the mortality of 2nd and 3rd burn injuries patients in Dr. SardjitoGeneral Hospital, Yogyakarta. This was a cross-sectional study conducted withinthe period of 2007-2011 using secondary data from the Department of MedicalRecords. Chi-square and logistic regression analysis were used to evaluate thecorrelation between the prognostic factors and the mortality. A p value < 0.05(95% confidence interval) was considered to be significant. A significantlycorrelation between age, burn injuries percentage, arrival time, inhalation trauma,hemoglobin level, albumin level, creatinine level, hematocrit level and the patient’smortality was observed in this study (p<0.05). However, the cause of burn injuriesand leukocyte count had no correlation with the patient’s mortality (p>0.05).Furthermore, patients with albumin level < 3.5 mg/dL, burn injuries percentage>50%, inhalation trauma and hospitalized in 24 hours after the incident were at22.98, 7.65, 3.0 and 4.59 times higher risk of mortality, respectively (p<0.05).In conclusion, albumin level, burn injury percentage, inhalation trauma and time ofarrival are prognostic factors affecting the mortality of the burn injuries patients.